Deep oxidative desulfurization of benzothiophene and dibenzothiophene with a peroxophosphotungstate–ionic liquid brush assembly. (14th July 2015) - Shi, Xian‐Ying; Sun, Man; Fan, Juan; Wang, Peng‐Min; Ma, Wen‐Juan; Wei, Jun‐Fa
<x xml:space="preserve">Abstract</x> A novel, efficient and reusable heterogeneous catalytic assembly of peroxophosphotungstate held in an ionic liquid brush was synthesized and an extraction and catalytic oxidative desulfurization (ECODS) procedure was developed for a model oil of benzothiophene (BT) and dibenzothiophene (DBT) using 30 wt% hydrogen peroxide as terminal oxidant and methanol as solvent under mild conditions. Several factors that affect sulfur removal were investigated in detail. The highest sulfur removal can reach 100% for BT in 7 h at 70 °C when the molar ratio of H2O2, S and catalyst is 10:1:0.025. The sulfur removal for DBT can also reach 100% in 4 h at 50 °C with the same molar ratio of H2O2, S and catalyst. The experimental results demonstrate that this ECODS process has no apparent scale‐up effect. The catalyst can be easily recovered (via simple filtration) and recycled five times without a significant decrease in activity. Copyright © 2015 John Wiley & Sons, Ltd.